SELF-ESTEEM AND ATTACHMENT STYLES AS PREDICTORS OF MARITAL SATISFACTION AMONG SECONDARY SCHOOL TEACHERS IN ILORIN METROPOLIS, KWARA STATE - Lateef Adegboyega (International Journal of Advanced Humanities Research)
This study investigated self-esteem and attachment styles as predictors of marital satisfaction among secondary school teachers in Ilorin metropolis, Kwara State. The study was a survey research. The population of this study comprised all secondary school teachers in Ilorin metropolis, Kwara State while a sample size of 200 teachers participated in the study. A questionnaire entitled “Self-esteem, Attachment Styles and Marital Satisfaction Questionnaire” (SASMSQ) was used to collect data for the study. Percentage was used to analyse the demographic data. Mean and rank order analysis was used to answer research questions while the four null hypotheses formulated were tested using regression, t-test, and ANOVA statistical techniques. The findings of the study revealed that teachers have high self-esteem, exhibit secure attachment styles, and experience high marital satisfaction. Self-esteem and attachment styles were found to significantly predict marital satisfaction. Based on the findings of this study, it was recommended that school administrators and policymakers implement workshops to boost self-esteem among teachers. Counsellors can employ techniques like cognitive-behavioural therapy and positive psychology interventions to reinforce healthy self-esteem. By promoting self-esteem and healthy attachment styles, educators can enhance marital satisfaction and overall well-being among teachers